1999
DOI: 10.1006/jcss.1999.1647
|View full text |Cite
|
Sign up to set email alerts
|

Two Queries

Abstract: We consider the question whether two queries SAT are as powerful as one query. We show that if

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…The two queries problem has been studied extensively, beginning with Kadin [14] who showed that P SAT [1] = P SAT [2] implies that the Polynomial Hierarchy (PH) collapses to the Σ P 3 level. Subsequent results [1,8,17,18] brought the collapse further down, to within ∆ P 3 .…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The two queries problem has been studied extensively, beginning with Kadin [14] who showed that P SAT [1] = P SAT [2] implies that the Polynomial Hierarchy (PH) collapses to the Σ P 3 level. Subsequent results [1,8,17,18] brought the collapse further down, to within ∆ P 3 .…”
Section: Introductionmentioning
confidence: 99%
“…A breakthrough in the proof techniques came when Hemaspaandra, Hemaspaandra and Hempel [13] showed that if the queries were made to a Σ P 3 oracle (instead of SAT), then PH ⊆ Σ P 3 which is a downward collapse. Buhrman and Fortnow [2] improved this technique and made it work for queries to a Σ P 2 oracle. Fortnow, Pavan and Sengupta [11] then showed that P SAT [1] = P SAT [2] =⇒ PH ⊆ S P 2 † Address: Department of Computer Science and Electrical Engineering, University of Maryland Baltimore County, 1000 Hilltop Circle, Baltimore, MD 21250, USA.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations